Fear extinction memory is negatively associated with REM sleep in insomnia disorder. Issue 7 (29th January 2020) - Bottary, Ryan; Seo, Jeehye; Daffre, Carolina; Gazecki, Samuel; Moore, Kylie N; Kopotiyenko, Konstantin; Dominguez, Jarrod P; Gannon, Karen; Lasko, Natasha B; Roth, Brittainy; Milad, Mohammed R; Pace-Schott, Edward F
Abstract: Study Objectives: Formation and maintenance of fear-extinction memories are disrupted in post-traumatic stress disorder (PTSD) and anxiety disorders. Sleep contributes to emotional memory consolidation and emotion regulation. Insomnia disorder (ID) is characterized by persistent sleep disturbance as well as rapid eye movement (REM) sleep abnormalities and often precedes or develops in parallel with PTSD and anxiety disorders. Here, we explore the impact of chronic poor sleep and sleep immediately following fear conditioning and extinction learning on preservation of extinction memories. Methods: Twenty-four ID age- and sex-matched to 24 healthy, good sleeper controls (GS) completed up to 2 weeks of habitual sleep monitoring with daily sleep–wake diaries and actigraphy, and then participated in a two-session fear conditioning, extinction learning and extinction recall procedure. Fear Conditioning and Extinction Learning occurred during session 1, followed by Extinction Recall approximately 24 hours later. Skin-conductance responses (SCR) and shock expectancies were recorded throughout all experimental phases to evaluate associative learning and memory. Overnight sleep between sessions 1 and 2 was recorded using ambulatory polysomnography. Results: ID showed greater physiological reactivity during Fear Conditioning. REM sleep physiology was associated with poorer extinction memory in ID but better extinction memory in GS. Conclusion: REM sleep physiology may differentially support emotional memory retention and expression in ID and GS. In the former, REM may enhance retention of fear memories, while in the later, REM may enhance the expression of extinction memories.